N-(Anthracen-9-ylmethyl)adamantan-1-amine - Fan, Wei-Qiang (International Union of Crystallography, 2012)
In the crystal stucture of the of the title compound, C(25)H(27)N, stong π–π interactions are found between adjacent anthracene fragments, with a shortest centroid–centroid distance of 3.5750 (9) Å.